Programmed Death Ligand-1 (PD-L1) is an independent negative prognosticator in Western-world gallbladder cancer - Albrecht, Thomas; Brinkmann, Fritz; Albrecht, Michael; Lonsdorf, Anke Susanne; Mehrabi, Arianeb; Hoffmann, Katrin; Kulu, Yakup; Charbel, Alphonse; Vogel, Monika Nadja; Rupp, Christian; Köhler, Bruno Christian; Springfeld, Christoph; et al. (Cancers, 2021)
Inhibition of the programmed cell death protein-1/ligand-1 (PD-1/PD-L1) axis has opened a new era in the treatment of solid cancers. However, there is no data on the expression and relevance of PD-L1 in Western gallbladder cancer (GBC). We assessed PD-L1 immunohistochemically in 131 GBC patients as Tumor Proportion Score (TPS), Immune Cell Score (IC) and Combined Positivity Score (CPS). Tumor cells expressed PD-L1 in a subset of 14.7% GBC patients at a TPS cut-off of 1%. Higher PD-L1 levels above 10% and 25% TPS were reached in 4.7% and 3.1% of GBC cases, respectively. At a 10% cut-off, TPS was associated with distinct histomorphological subtypes and correlated with poor tumor differentiation. Survival analysis revealed a TPS above 10% to be a highly significant and independent negative prognosticator in GBC. PD-L1 expression was associated with increased CD4+, CD8+ and PD-1+ immune cell densities. In 14.8% of the cases, scattered immune cells expressed T-cell immunoreceptor with Ig and ITIM domains (TIGIT), which was correlated to tumoral expression of its ligand CD155. We here show that a high PD-L1 expression confers a negative prognostic value in Western-world GBC and highlight the TIGIT/CD155 immune checkpoint as a potential new target for GBC immunotherapy.